Naive bayes algorithm based e-mail spamming filtering system - Lee Kim Hao (2022)
E-mail spam although not against the law of federation, this issue still annoying every user and clogging up the space of their mailbox. With the inspiration of previous happen spam issue in Universiti Malaysia Sabah official account and increasingly spam issue causing nuisance toward e-mail users. In this final year project, author will be looking for developing a spam filtering system that will scan and filter out spam message that might be sent from any other users with checking the keyword that record toward the system. According to the research found, there are various of spam filtering technology such as Content Based Filters, Bayesian Based Filters, Whitelist or Blacklist Filters, and Community Filters. Certain problem found by author on the common spamming content such as phishing scam content, irrelevant or fake advertising content and harassment content. The objective of this project is designing a spam filtering system using content-based Bayesian technique to classify and remove spam message to junk folder. This project final product is target toward user frequently using e-mail and the module containing login/logout authentication, home page and mailbox. Author conducted Agile model Scrum for One method toward this project in order to accomplish the project. A final version of product had been implemented in different directory without integrating due to limited skill possessed though putting away the integrating issue the project considered partially complete as it had fulfilled some of the objectives listed.